A preliminary survey of marine cave habitats in the Maltese Islands - Knittweis, L.; Chevaldonné, P.; Ereskovsky, A.; Schembri, P.J.; Borg, J.A. (Xjenza Online, 2015)
The Mediterranean Sea is a hotspot for marine biodiversity. Past studies of Mediterranean marine caves have revealed the unique biocoenotic and ecological characteristics of these habitats, which are protected by European Union legislation. The Maltese Islands have an abundance of partially and fully submerged marine caves with different geomorphological characteristics, yet there have been no systematic studies on these habitats and their associated species. This study is a first synthesis of existing information on the biotic assemblages and physical characteristics of Maltese marine caves. The work combines a review of the available information with a preliminary survey of some marine caves in Gozo, during which several species were recorded for the first time for the Maltese Islands. Characteristic species recorded from local marine caves are high- lighted, including several species of red and brown algae, sessile invertebrates including bryozoans, ascidians and sponges, and mobile forms including crustaceans and fish. A marked zonation from the cave entrance to the inside of the caves was identified: photophilic algae at the mouth of the cave are progressively replaced by more sciaphilic species, followed by a middle section dominated by sessile invertebrates, and then a completely dark inner section that is mostly devoid of sessile organisms. Several species protected by national and international legislation were found to occur.